2008
DOI: 10.1063/1.2839577
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic forces involving deformable interfaces at nanometer separations

Abstract: A model is developed to describe the dynamic forces acting between two deformable drops, or between one drop and a solid surface, when they are in relative axisymmetric motion at separations of Շ100 nm in a Newtonian liquid. Forces arise from hydrodynamic pressure in the draining liquid film that separates the interfaces and from disjoining pressure due to repulsive or attractive surface forces. Predictions of the model are successfully compared with recent experimental measurements of the force between two mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
161
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(168 citation statements)
references
References 40 publications
7
161
0
Order By: Relevance
“…This is a generalization of a similar result given earlier for drops with the same interfacial tension [93]. Unfortunately that result contained a typographical error.…”
Section: Force-displacement Formula For Afm Experimentssupporting
confidence: 48%
“…This is a generalization of a similar result given earlier for drops with the same interfacial tension [93]. Unfortunately that result contained a typographical error.…”
Section: Force-displacement Formula For Afm Experimentssupporting
confidence: 48%
“…The quantity α is a known function of the radii ðR c ;R s Þ and contact angles ðθ c ;θ s Þ of the bubbles (16). This boundary condition follows from a constant volume constraint on the bubbles and is a key and crucial difference between our model for AFM experiments (16) and previous work.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, we observed that our experimental results were consistent with bubble surfaces that are immobile as described by the no-slip hydrodynamic boundary condition. To facilitate comparisons with our collision experiments on the AFM, an appropriate description of the collision protocol between two incompressible but deformable bubbles also had to be developed to provide the correct boundary condition to augment the governing equations (16,40).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…given results for the interaction between two identical drops, it is straightforward to generalize to the case of interacting dissimilar drops or to describe how drops interact with solids 17 .…”
Section: Since For Approaching Drops H(t) Is Decreasing the Analyticmentioning
confidence: 99%